Moderator effect of household income on parental investment in Malaysia - Abdullah, Nuraini (2019)
Parents assume the heaviest responsibility ever to prepare children for a brighter life. It is important for parents to understand the needs of the children so that they succeed in adulthood. Therefore, the study focuses on predicting the factors that contribute parental investment. Parental characteristics, child-rearing practices, parental purchasing behaviour, and financial strain are among the variables that were tested to explore the predictor of parental investment while the moderating effect of household income was examined to establish household income differences pertaining the influences of independent variables on parental investment. The core theory pertaining to this research is the Theory of Human Capital. Meanwhile, the Child Quantity-Quality (Q-Q) Trade-Off Theory, the Parent-Offspring Conflict Theory (POCT), and the ABCD-XYZ Resource Management Model of Crisis/Stress are supportive theories serving as the basis for the theoretical framework. This study used secondary data from a research entitled “Cost of raising a child: Policy implication” where 2,182 samples of parents with children below six years old from low and middle-income families were selected. The analysis, which had used Pearson correlation, revealed positive relationships among variables, namely child-rearing practices (r=.110, p<.000), parental purchasing behaviour (r=.188, p<.0.000), parental purchasing behaviour (consumption-related preferences), (r=.194, p<.000), and parental purchasing behaviour (consumer skills), (r=.079, p<.000), whereas a negative relationship was reported for financial strain (r=-.111, p<.000) with parental investment. Binary logistic regression analysis revealed factors predicting parental investment. Parental characteristics, namely the level of education, ethnicity, and the number of children per household were significant, while others variables such as child-rearing practices, parental purchasing behaviour (consumer related preferences), and financial strain also indicate a significant contribution to parental investment. Apart from that, PROCESS Macro version 3.3 in SPSS was used to examine the simple moderating effect of household income based on hypothesis. The moderation effect of household income revealed that none of parental characteristics such as parents’ level of education, ethnicity, and number of children per household were significant. Other than that, parental purchasing behaviour (consumer related preferences) and financial strain were found to be not significant. Only child-rearing practices were found to have significant moderator effect on parental investment. In summary, this study supports the importance of parental investment among parents, especially for those from low and middle-income families. As such, this study underline some applicable implication to facilitate the parents in terms of children investment. The recommendations for future research on parental investment are also pointed out.